2012
DOI: 10.1007/s10534-012-9584-0
|View full text |Cite
|
Sign up to set email alerts
|

Ni2+ effects on Nicotiana tabacum L. pollen germination and pollen tube growth

Abstract: To investigate the mechanisms of Ni(2+) effects on initiation and maintenance of polar cell growth, we used a well-studied model system-germination of angiosperm pollen grains. In liquid medium tobacco pollen grain forms a long tube, where the growth is restricted to the very tip. Ni(2+) did not prevent the formation of pollen tube initials, but inhibited their subsequent growth with IC(50) = 550 μM. 1 mM Ni(2+) completely blocked the polar growth, but all pollen grains remained viable, their respiration was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A dose-effect linearity was also found for apricot and cherry pollen [56]. Nickel shows combined effects, as it does not block germination but prevents pollen tube growth [57]. Lead treatment causes profound alterations in pollen tubes, which show cessation of growth and uneven distribution of cell wall components, most likely by targeting the cytoskeleton [58].…”
Section: Heavy Metal-induced Stressmentioning
confidence: 88%
“…A dose-effect linearity was also found for apricot and cherry pollen [56]. Nickel shows combined effects, as it does not block germination but prevents pollen tube growth [57]. Lead treatment causes profound alterations in pollen tubes, which show cessation of growth and uneven distribution of cell wall components, most likely by targeting the cytoskeleton [58].…”
Section: Heavy Metal-induced Stressmentioning
confidence: 88%
“…Previous studies confirmed the direct effect of serpentinite soils on inflorescence size and height, in response to the lower amount of nutrients in the substrate [ 67 ]. The presence of heavy metals such as Ni in the substrate has a negative effect on plant reproduction [ 68 ]. In plants, the evolutionary response to environmental stress is slow growth, and consequently low nutrient requirements, with the drawback of lower overall productivity.…”
Section: Discussionmentioning
confidence: 99%
“…We should note, however, that Ni may be complexed to organic molecules (Homer et al, 1991; Leitenmaier and Küpper, 2013), so the actual Ni exposure from germinated S. polygaloides pollen may be less than estimated. Nonetheless, there are reports in the literature for both inhibitory (e.g., Nicotiana tabacum L.; Tuna et al, 2002; Breygina et al, 2012) and stimulatory effects of Ni +2 ions or other heavy metals (e.g., Cd, and Fe) on pollen germination and tube growth Sawidis and Reiss, 1995; Xiong and Peng, 2001; Tuna et al, 2002). So it is possible that greater pollen germination by M. guttatus in response to S. polygaloides pollen receipt in our study reflects stimulation by Ni or through its effects on metabolism (Welch, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…While metal accumulators are often adapted to soils with high concentrations of heavy metals, these metals not only negatively affect the growth of intolerant species but can also cause abnormalities in their gamete and embryo development (Sabrine et al, 2010; Mohsenzadeh et al, 2011). Moreover, direct exposure to some heavy metal ions (e.g., Ni) can inhibit pollen germination and pollen tube growth, leading to decreased seed production (Malan and Farrant, 1998; Tuna et al, 2002; Breygina et al, 2012). As recent work has shown that Ni can accumulate in pollen of hyperaccumulators (Meindl et al, 2014; Sánchez‐Mata et al, 2014), Ni may be introduced to heterospecific pistils via interspecific pollen transfer.…”
mentioning
confidence: 99%